2003
DOI: 10.1097/00063110-200309000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Electrocerebral silence with preserved but reduced cortical brain perfusion

Abstract: Isoelectric electroencephalogram in conformance with clinical findings is strongly suggestive of brain death. In clinical practice, isoelectric electroencephalogram in not-brain-dead patients is rarely seen. We report on a 53-year-old patient who suffered ischaemic encephalopathy after cardiopulmonary arrest. He had residual brainstem function with sufficient spontaneous breathing and evidence of cerebral blood flow on single photon emission computed tomography scan, but his electroencephalogram was isoelectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…A nonenhanced CT scan can also provide information about structural lesions, stroke, or intracranial hemorrhage that may have contributed to cardiac arrest. 268,269 Other less utilized and investigated neuroimaging modalities have included single-photon emission computed tomography, 253,267,270 cerebral angiography 244 and transcranial Doppler 240 A nuclear imaging study observed that abnormal tracer uptake in the cerebral cortices was associated with poor outcome in one case report. 248 Despite tremendous potential, neuroimaging has yet to be proved as an independently accurate modality for prediction of outcome in individual comatose survivors of cardiac arrest and specific neuroimaging modalities cannot be recommended for predicting poor outcome after cardiac arrest.…”
Section: Neuroimagingmentioning
confidence: 99%
“…A nonenhanced CT scan can also provide information about structural lesions, stroke, or intracranial hemorrhage that may have contributed to cardiac arrest. 268,269 Other less utilized and investigated neuroimaging modalities have included single-photon emission computed tomography, 253,267,270 cerebral angiography 244 and transcranial Doppler 240 A nuclear imaging study observed that abnormal tracer uptake in the cerebral cortices was associated with poor outcome in one case report. 248 Despite tremendous potential, neuroimaging has yet to be proved as an independently accurate modality for prediction of outcome in individual comatose survivors of cardiac arrest and specific neuroimaging modalities cannot be recommended for predicting poor outcome after cardiac arrest.…”
Section: Neuroimagingmentioning
confidence: 99%
“…Single photon emission CT (SPECT) is supported by 3 LOE P5-studies 990,1006,1009 and is opposed by 1 LOE P2-study. 1010 The timing of SPECT in these studies ranged from 1 to 23 days after sustained ROSC.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…MRI showed similar findings, but was superimposed by movement artefacts. In repeated EEG no electrical brain activity was detected indicating severe cortex damage, which was also demonstrated by SPECT with strongly reduced cortex perfusion [1]. Antibiotic treatment included ceftriaxon, ampicillin and gentamicin leading to resolution of the inflammatory response.…”
mentioning
confidence: 88%